1981
DOI: 10.1002/jrs.1250110207
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of the phase transition in RbHSO4

Abstract: Raman spectra of RbHSO, have been recorded in the temperature range from 6 K to the melting point, 480 K. Analysis of the spectra show that the second order phase transition, at 264 K, is of the order-disorder type. NO soft mode was found. The evolution of the v(0-H) mode frequency with temperature, is consistent with a change of orientation of the hydrogen bonds connecting the disordered SO,-O(H) groups. The spectra are also consistent with the existence of a prototype phase which hs3 been assumed to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…These results, along with earlier spectroscopic work by Ozaki (1980) and Toupry et al (1981), are consistent with dynamic disorder in the two oxygen positions. Two O atoms of HS(1)O 4 À can be refined against the neutron data obtained in the present study over two split positions each with refined occupancies of 0.51 (2) and 0.49 (2) for O20/21 and 0.50 (2) for O30/31.…”
Section: Paraelectric Phase Isupporting
confidence: 87%
See 2 more Smart Citations
“…These results, along with earlier spectroscopic work by Ozaki (1980) and Toupry et al (1981), are consistent with dynamic disorder in the two oxygen positions. Two O atoms of HS(1)O 4 À can be refined against the neutron data obtained in the present study over two split positions each with refined occupancies of 0.51 (2) and 0.49 (2) for O20/21 and 0.50 (2) for O30/31.…”
Section: Paraelectric Phase Isupporting
confidence: 87%
“…They conclude that one HSO 4 À anion shows disorder in two O-atom positions rather than all four. A Raman spectroscopy study by Toupry et al (1981) found the temperature dependence of the O-H frequency to be consistent with a change in ionic orientation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The spectra may be compared with those of H2S04,' KHSO; and RbHS0,. 6 The bridging of the iron atoms by the SO:-ions lengthens the two S-0 distances and shortens the free S=O bonds. In a first approximation the SO, groups can be considered as tetrahedral and in a second approximation of C2, symmetry.…”
Section: Csife(so)] Rhombohedra1 Phase R3c C!"mentioning
confidence: 99%
“…Furthermore, low-temperature Raman spectroscopy studies on the compound revealed the transition to be of the order−disorder type, where the room temperature disordered paraelectric phase is going into an ordered ferroelectric phase after the transition temperature. 12 Gesi and Ozawa have studied the pressure-dependent dielectric constant of RbHSO 4 and found a ferroelectric transition around 0.4 GPa and another transition at 0.75 GPa. 1 They assumed that the crystal structure of RbHSO 4 between 0.4 and 0.75 GPa pressure to be monoclinic with space group Pc, which is the same as the structure at the low-temperature ferroelectric phase.…”
Section: ■ Introductionmentioning
confidence: 99%